2007
DOI: 10.1007/s00114-007-0257-8
|View full text |Cite
|
Sign up to set email alerts
|

Queue up, please! Spermathecal filling in the rove beetle Drusilla canaliculata (Coleoptera, Staphylinidae)

Abstract: Most studies on insect sperm motility have been conducted in vitro using artificial environments outside the animal's body. Only little is known about the function of motile insect sperm at different sites within the male or female genital tracts. We dissected genital tracts of female rove beetles (Drusilla canaliculata) to show that spermatozoa use their own motility to migrate from the spermatophore into the spermatheca. Our dissection method allowed direct observation and filming of the spermathecal filling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The outer diameter of MEG is too small (less than 2 µm; Matsumura & Akimoto, 2009) to go through the MEG for plural spermatozoa at one time. As shown by Werner et al. (2007) for the rove beetle Drusilla canaliculata , such a small diameter of the extremely elongated MEG can make it possible for spermatozoa to push themselves off the tube wall and migrate into the spermathecal capsule.…”
Section: Discussionmentioning
confidence: 99%
“…The outer diameter of MEG is too small (less than 2 µm; Matsumura & Akimoto, 2009) to go through the MEG for plural spermatozoa at one time. As shown by Werner et al. (2007) for the rove beetle Drusilla canaliculata , such a small diameter of the extremely elongated MEG can make it possible for spermatozoa to push themselves off the tube wall and migrate into the spermathecal capsule.…”
Section: Discussionmentioning
confidence: 99%
“…A similar scenario might occur in relation to spermathecal duct length and sperm length. Indeed, Werner et al . (2007) have shown that the spermatozoa of Drusilla canaliculata (Coleoptera: Staphylinidae) interact with the spermathecal duct to gain progressive motility.…”
Section: Discussionmentioning
confidence: 99%
“…The axonemal wave would then act against the duct wall rather than the surrounding fluid, leading to a crawling motion instead of swimming. Although not yet investigated systematically, observations on Drusilla canaliculata sperm movement within the female genital tract add support to this theory (Werner et al , 2007).…”
Section: In Vitro Motility Versus In Vivo Motilitymentioning
confidence: 95%
“…Spermatozoa of the dipteran Megaselia scalaris for example, exhibit the double helical motility pattern when released in buffer, but express a more random motility pattern, including strong bending of the tail, when observed in pockets of the female genital tract (Curtis & Benner, 1991). In the rove beetle Drusilla canaliculata (Fabricius) the differences are even more marked (Werner et al , 2007). When released in buffer, spermatozoa of this species are unable to progress in the medium and show only feeble movement of the flagellum.…”
Section: In Vitro Motility Versus In Vivo Motilitymentioning
confidence: 99%